Sustainable Tourism: Evidence from Lake Toba in North Sumatra, Indonesia - Kalu Kingsley Anele; Chika Clara Sam-Otuonye (Centre For Tourism Planning and Development, 2021)
Tourism has become an important sector in some national economic development, especially in Indonesia. In Indonesia, the tourism sector is one of the biggest non-oil foreign exchange-earners. Consequently, the Indonesian government has introduced laws, policies, and regulations to bolster the sector. Specifically, Lake Toba in North Sumatra is a famous coastal tourist destination in Indonesia, which attracts both local and foreign tourists. The objectives of this research are to examine coastal tourism in Indonesia and address possible measures to achieve sustainable coastal tourism in Lake Toba. The methodology adopted in this research includes a qualitative approach with descriptive and dialectical analysis. Moreover, the data used are adopted from literature, tables, pictures, and documentary reviews. In the course of the research, it was discovered that many factors threaten sustainable tourism development in Lake Toba, particularly lack of and access to infrastructure, inadequate funds, among others. The result of the research reveals that government laws and policies and recommendations by scholars significantly strengthen sustainable tourism in Lake Toba. In concluding the research, it was argued that due to the economic and social-cultural importance of tourism to the development of Indonesia, it is imperative to effectively implement the laws, policies, and recommendations outlined in the paper.